USE OF THE BACTERIUM Rhodococcus fascians FOR OPTIMIZATION OF BLACK WATTLE SHOOT FORMATION - EISFELD, Cristiane De LOYOLA; RIBAS, Luciana LOPES FORTES; QUOIRIN, Marguerite (Scientia Agraria, 2004)
Black wattle (Acacia mearnsii) is planted by small farmers in South of Brazil. This species provides cellulose, paper and tannin. Considering the economical importance of black wattle, clonal propagation techniques need to be assessed. The technique described in the present work uses the bacterium Rhodococcus fascians to induce the formation of multiple shoots. When in vitro germinated black wattle plantlets are infected with R. fascians, leafy galls consisting of multiple meristems and bud primordia develop at apical buds. In order to induce the formation of shoots, leafy galls were excised from the plantlets and cultured in culture media containing three-fourth of mineral salts of MURASHIGE and SKOOG (1962) [8] medium (MS), full MS vitamins and organic compounds, 20 g.L-1 sucrose and 7 g.L-1 agar. Three experiments were conducted. In the first one, activated charcoal (AC) was added (2g.L-1) or not to the culture medium. In the second one, three concentrations (0.29; 1.44 e 2.89 mM) of gibberellic acid (GA3) were tested and compared to a control without GA3. In the third one three concentrations (1.0; 2.0 e 5.0 mM) of 2,3,5-triiodobenzoic acid (TIBA) were supplemented to the culture medium. There was no statistical difference between shoot formation on AC containing media and control media. In the second experiment, it was observed that addition of 1,44 mM GA3 to the culture medium induced a higher, but not significant, mean number of shoots. When 2 or 5 mM of TIBA was added to the culture media, the number of shoots per leafy gall was 2.91 and 2.48 respectively, higher than on control medium (1.48).